2022
DOI: 10.4103/aian.aian_589_21
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barre Syndrome and Antibodies to Arboviruses (Dengue, Chikungunya and Japanese Encephalitis)

Abstract: Objective: The aim of this study was to detect the presence of IgM antibodies against dengue (DEN), chikungunya (CHIK) and Japanese encephalitis (JE) in the serum and CSF of patients with Guillaine-Barre syndrome (GBS). Methods: GBS patients (>12 years of age) were included after informed consent. Data on history, clinical manifestations, treatment details, and outcome were collected. Serum and CSF were tested for IgM antibodies against DEN, CHIK, and JE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(28 reference statements)
0
2
0
2
Order By: Relevance
“…The bacterial culture showed the presence of Klebsiella pneumoniae, which was resistant to all antibiotics except for fosfomycin, while the fungal culture did not yield any results. A retrospective study by Amalnath et al [30] showed that 22 patients developed large cavities 2 to 4 weeks after experiencing symptoms. None of these patients were on mechanical ventilation, but 18 of them died within a few days of discovering the cavities.…”
Section: Discussion and A Brief Review Of The Literaturementioning
confidence: 99%
“…The bacterial culture showed the presence of Klebsiella pneumoniae, which was resistant to all antibiotics except for fosfomycin, while the fungal culture did not yield any results. A retrospective study by Amalnath et al [30] showed that 22 patients developed large cavities 2 to 4 weeks after experiencing symptoms. None of these patients were on mechanical ventilation, but 18 of them died within a few days of discovering the cavities.…”
Section: Discussion and A Brief Review Of The Literaturementioning
confidence: 99%
“…GBS is the most frequent cause of acute flaccid paralysis worldwide and is often preceded by an infectious disease. Flavivirus infections are also responsible for a significant number of GBS patients, especially in highly endemic countries ( 36 38 ). However, GBS is rarely reported after JEV infection and is limited to case reports.…”
Section: Discussionmentioning
confidence: 99%
“…A Síndrome de Guillain-Barré (SGB) define-se como uma polirradiculopatia imunomediada caracterizada por um quadro de paralisia ascendente arreflexa podendo evoluir, com pior prognóstico, para fraqueza muscular respiratória. (Pari et al, 2022). Nesse contexto, um extenso conjunto de evidências inferidas respalda a natureza autoimune da síndrome.…”
Section: Introductionunclassified